The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1149/1.1566020
|View full text |Cite
|
Sign up to set email alerts
|

A Duplex Mechanism-Based Model for the Interaction Between Chromate Ions and the Hydrated Oxide Film on Aluminum Alloys

Abstract: In order to understand more clearly the nature of the anodic film formed on aluminum and its alloys, and the mechanism of inhibition of corrosion by chromates, a novel investigation has been made on the anodic film formed on AA1060 using X-ray photoelectron spectroscopy. The goal has been to elucidate whether the interaction of CrO 4 2Ϫ on Al alloy surfaces is in certain aspects analogous to that of MoO 4 2Ϫ on stainless steel surfaces and investigate whether a bipolar mechanism is applicable to aluminum surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 108 publications
1
26
0
Order By: Relevance
“…We have earlier shown that aluminum hydroxide films, which impart lesser corrosion resistance than aluminum oxide passive films, are susceptible to chloride ingress, while aluminum oxide films formed by deprotonation of hydrated films by chromate are protected. 57 Hence, we consider this hydration to be the reason for the observed activation.…”
Section: Resultsmentioning
confidence: 99%
“…We have earlier shown that aluminum hydroxide films, which impart lesser corrosion resistance than aluminum oxide passive films, are susceptible to chloride ingress, while aluminum oxide films formed by deprotonation of hydrated films by chromate are protected. 57 Hence, we consider this hydration to be the reason for the observed activation.…”
Section: Resultsmentioning
confidence: 99%
“…With regards to the progression of Cr(III) adsorption onto nanoboehmite surfaces, they [203] concluded that initial Cr(III) adsorption onto nanoboehmite under alkaline conditions occur by hydroxyl ligand exchange which leads to inner-sphere binding of Cr(OH) 4 −monomers, but at Cr(III) concentration in solution >20 ppm these monomers polymerize into clusters. Chromate ions are reported by several authors [204][205][206][207] to inhibit both hydration and deprotonation of anodic oxide films on aluminum.…”
Section: What Makes Chromium Sealing Unique and Accounts For Its Actimentioning
confidence: 99%
“…All XPS Spectra were taken at 90 • take off angle with respect to the sample surface and all spectra were corrected for charging by using the C 1 s line of adventitious carbon at 284.6 eV as a reference. All curve fitting followed the methods outlined by Savitsky and Golay [11], and Sherwood [12], as well as procedures developed over the years by Halada and Clayton [13][14][15] using CASA software version 1.001. XPS was performed on select samples to determine the surface (depth analysis 5-10 nm) chemical changes taking place on the spool material and the resulting printed 3D structures.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%